A.P. Cowie. English Dictionaries for Foreign Learners: A History - Louw, Phillip (Lexikos, 2005)
In the mid 1990s the evolution of the English learner's dictionary reached a zenith with the appearance on the market of four advanced-level monolingual learners' dictionaries. Three of these were existing works, i.e. the Oxford Ad-vanced Learner's Dictionary of Current English (henceforth ALD), the Longman Dictionary of Contemporary English (henceforth LDOCE) and the Collins CO-BUILD English Language Dictionary (henceforth COBUILD), which marked, to differing extents, significant departures from the lexicographical procedures followed by their predecessors. The last one, the Cambridge International Dic-tionary of English (henceforth CIDE), was a completely new dictionary. This highly productive burst of lexicographical energy was also the catalyst for an even more productive and sustained body of metalexicographical research and writing that dealt with the topic of learners' dictionaries.